Gbp2 driving macrophages dynamics in murine heart transplant - Zhang, Baotong; Ji, Wenbin; Wang, Duowei; Chen, Guoshan; Xiong, Wenhao; Qi, Feng (Tissue & cell, 2025)
Organ transplantation is a vital treatment for patients with end-stage organ diseases, and macrophages play a key role in the rejection process. This study seeks to pinpoint key genes responsible for the dynamic changes in macrophages during rejection and to evaluate their impact on macrophage polarization through bioinformatics analysis. We selected single-cell sequencing data of mouse heart transplant models from Genome Sequence Archive to construct a dynamic landscape of immune cells during acute rejection. Key genes involved in macrophage changes were screened using pseudotime analysis and hdWGCNA. The mouse heart transplant models also were established to validate changes of the key genes during rejection. Bioinformatics analysis identified Gbp2 as the key gene driving macrophage dynamics during rejection, which was also confirmed in another dataset showed Gbp2 levels increased in macrophages during acute rejection. Further experiments validated the upregulation of Gbp2 in both tissues and macrophages during acute rejection, and in vitro experiments confirmed Gbp2 increasing in M1 macrophages. Gbp2 is a key gene that regulates macrophage polarization during acute rejection, making it a potential therapeutic target for the acute rejection. •The dynamic immune cell landscape after heart transplantation.•Macrophages Demonstrated Transcriptional and Functional Heterogeneity.•Bioinformatics analysis combined trajectories with hdWGCNA.•Gbp2 was upregulated in M1 Macrophages than M0 Macrophages.